A Lanthanide luminescent cation exchange material derived from a flexible tricarboxylic acid 2,6-Bis(1,2,3-Triazol-4-yl)pyridine (btp) tecton - Gunnlaugsson, Thorfinnur; Schmitt, Wolfgang (My University, 2018)
The synthesis of the three-dimensional metal–organic framework material, [Zn7L6]·(H2NMe2)4·(H2O)45 (1), derived from a flexible tricarboxylic acid 2,6-bis(1,2,3-triazol-4-yl)pyridine (btp) ligand, is presented. The btp ligand, H3L, adopts a three-dimensional hydrogen bonding network in the crystalline state through a combination of carboxylic acid dimer and syn–anti-btp/carboxylic acid hydrogen bonding synthons. The Zn(II) species 1 exhibits a three-dimensional framework structure with the rare crs topology and contains linear and undulated solvent channels extending in three dimensions. The guest exchange and gas adsorption properties of 1 were investigated; herein we demonstrate the exchange of dimethylammonium cations from the as-synthesized material with cationic guest molecules in the form of dyes and luminescent Ln(III) ions. Sensitization of Eu(III) and Tb(III) inside the porous network of 1 was achieved upon cation exchange, with a view toward developing functional luminescent materials.